Thermodynamic modelling of the V–Ti–B system. (December 2022) - Yazlak, M.; Christ, H.-J.; Yang, W.; Hasemann, G.; Krüger, M.; Gorr, B.
Abstract: Thermodynamic modelling is an effective approach to accelerate the development of novel materials such as V-based alloys. In the present work, the results of thermodynamic modelling of the ternary system V–Ti–B using the "CALculation of PHAse Diagrams" (CALPHAD) method are presented. The thermodynamic descriptions of the binary systems V–Ti, V–B, and Ti–B are based on available publications whereas thermodynamic parameters for the ternary system stem from the iterative approximation to the experimental investigations, which further serve for verifying the calculated phase diagram. Thus, eight different alloys in the compositional range of 10–40 at.% Ti and B were analyzed aiming at identifying the evolving phases. A set of thermodynamic parameters is proposed. The calculated isothermal phase diagram at 1673 K exhibits a high degree of agreement with the literature and experimental observations. In our further work, the thermodynamic data generated in this study will be useful to develop the quaternary V–Ti–Si–B system.